Finansial Feasibility Analysis of Copra Processing Business at Jeruju Besar Village Sungai Kakap District Kubu Raya Regency - Artadewa, Azmi; Yurisinthae, Erlinda; Suyatno, Adi (Jurnal Sains Pertanian Equator, 2020)
This research aim is to analyze financial feasibility of copra processing enterprises in the Jeruju Besar village, Sungai Kakap district, Kubu Raya regency . The research uses data primary and secondary data with the number of respondents as many as 13 people and wearing a method of the census. The value of the discount factor is 7%. Analysis of the data used was analysis feasibility financial as Net Present Value (NPV), Net Benefit-Cost ratio ( Net B/C), Internal Rate of Return (IRR), Payback Period (PP) and sensitivity analysis. The research results show that it is still appropriate to copra processing enterprises followed by the value of Net Present Value (NPV) as much as Rp. 172.935.815, Net Benefit-Cost ratio ( Net B/C) is 2,996, Internal Rare of Return (IRR) is 44,5 %, and scores of the Payback Period (PP) is 0,27 years or about 2 months and 7 days. Despite the Net Present Value (NPV) , So it could be conclusion that the processing enterprises of corpa is still worth to be operations. In the analysis sensitivity, researchers chose the scenario 2 scenario 45 copra price increase of percent and scenario wages increase employment of 2 %. The results show that the two scenarios analisiss senstivitas sensitivity analysis is still worth planted. Key Words : financial feasibility, copra processing, discount factor, Net Preseent Value (NPV), Net Benefit-Cost Ratio (Net B/C), Internal Rare of Return (IRR), Payback Period (PP), Sensitivity Analyze.